2006
DOI: 10.1007/s11431-006-0129-z
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculation of dehydrogenating properties of MgH2-V systems

Abstract: Based on experimental results in which VH 0.81 /MgH 2 interface was found during the process of mechanically milling MgH 2 +5at%V nanocomposite, a VH/MgH 2 interface is designed and constituted in this work. A first-principles plane-wave pseudopotential method based on Density Functional Theory (DFT) has been used to investigate the vanadium alloying effects on the dehydrogenating properties of magnesium hydride, i.e., MgH 2 . A low absolute value of the negative heat of formation of VH/MgH 2 interface compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…[7], the resulting heats of formation of the studied systems are listed in Table 1. It is shown, on the one hand, that DH ¼ À63.018kJ/mol.H 2 for MgH 2 structure is close to the theoretical values obtained using different methods: À63.18kJ/mol.H 2 [11], À75.99 kJ/mol.H 2 [12], À69.51 kJ/mol.H 2 [13], À82 kJ/mol.H 2 [21], À54.4 KJ/mol.H 2 [22], À71.98 KJ/mol.H 2 [23] and also close to the experimental value À76.15 ± 9.2kJ/ mol.H 2 obtained in Ref. [24].…”
Section: Thermodynamic Properties From Dft Methodsmentioning
confidence: 99%
“…[7], the resulting heats of formation of the studied systems are listed in Table 1. It is shown, on the one hand, that DH ¼ À63.018kJ/mol.H 2 for MgH 2 structure is close to the theoretical values obtained using different methods: À63.18kJ/mol.H 2 [11], À75.99 kJ/mol.H 2 [12], À69.51 kJ/mol.H 2 [13], À82 kJ/mol.H 2 [21], À54.4 KJ/mol.H 2 [22], À71.98 KJ/mol.H 2 [23] and also close to the experimental value À76.15 ± 9.2kJ/ mol.H 2 obtained in Ref. [24].…”
Section: Thermodynamic Properties From Dft Methodsmentioning
confidence: 99%
“…In addition, based on the research of Im3̅ m CaH 6 and YH 6 with H clathrates, , Liang et al have reported that the ternary hydride Fd 3̅ m CaYH 12 has a pretty high T c (at 200 GPa, T c = 258 K) . However, the previous research on the Mg–V–H ternary systems mainly focused on the field of hydrogen storage, and the structure evolution and properties of ternary Mg–V–H hydrides are less involved under high pressure. Based on the above viewpoint, we selected the ternary Mg–V–H hydride as an aim to investigate its structure evolution and superconductivity under high pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Using the same code as in the supercell model, the total energy of V atoms is calculated to be -1979.06 eV. The total energy of H 2 is -2.320 Ry (-31.57 eV) [22] obtained by using the von Barth-Hedin exchange-correlation potential. The heat of formation of the VH 2 interfacial model is -65.61 kJ/mol (-0.68 eV) calculated from eq.…”
Section: Heat Of Formationmentioning
confidence: 99%